Strategy Development for a Successful Change Implementation at Barloworld - Costa, King; Nyoni, Abner (My University, 2020)
Businesses exist to generate profits for the shareholders, pay taxes and to pay their employees. Therefore, managers constantly look for better ways to maximise profits. In this quest they must continuously improve operations and use technology where possible and necessary. This endeavour calls for business improvement and automation as much as possible. Invariably this affects employees who might be frightened by changes in the organisation. Employees must be thought of and catered for when a change takes place in their work environment. Most organisations are faced with a never-ending dilemma of having to deal with change cycles that happen at a high frequency rate and high failure rate. The objectives of the study are to determine how change process is embraced at Barloworld; to ascertain if change process is formalised at Barloworld; to examine the need for organisations to develop a change framework; and to establish the elements of a framework for a successful change implementation. For this research a qualitative methodology was used. Semi-structured interviews were conducted with the participants using Zoom for these interviews and for recording the sessions. These interview sessions were conducted for a period of two weeks. The collected data was thoroughly analysed using thematic analysis to get to the findings, conclusions and recommendations. The findings of the study revealed that there is an understanding of the need for change at Barloworld, however there is further inference suggesting that the processes of change management could have been handled better. Participants indicated support and buy-in to an eminent change. Inadequate communication flow emerged as a cause and an impediment to successful change implementation. Review of participants’ statements in vivo indicated that a recent exercise of change management lacked a guiding tool such as a framework from employees’ perspective. A framework for change management at Barloworld needs to be visible, communicated and inclusive.
Keywords: Change management; Change Strategy; Communication; Employees; Leaders; Managers; Organizations